Animal Vision: Seeing the Earth's magnetic field. Issue 2 (February 2021) - Daly, Ilse
Abstract : Of all the senses, magnetoreception, the ability to detect the Earth's magnetic field, is probably the most mysterious and least well-understood, says Dr Ilse Daly .